Ultra-Low-Dose Radiotherapy for Palliation of Mycosis Fungoides - Aral, İpek Pinar; Göçer Gürok, Neşe; Konuk, Aykut O?uz; Üçer, Özlem (Hindawi Limited, 2020)
Introduction. Mycosis fungoides (MF) is a form of primary cutaneous T-cell lymphomas, and radiotherapy (RT) has been used to treat localized/limited lesions of MF. In this case report, the results of low-dose RT applied for palliative purpose are shared. Case Report. A 70-year-old male patient was admitted to the outpatient clinic 7 months ago with a generalized itchy rash. The result of the biopsy was reported as mycosis fungoides. Systemic treatment was not performed due to comorbid diseases. The hemibody RT was applied. 2 Gy was given per fraction, with a total dose of 6 Gy. The significant clinical relief was observed with 6 Gy RT. The patient died due to multiorgan failure 2 months later, and no recurrence was observed. Conclusion. The palliation was achieved in the advanced MF patient with fractionated 6 Gy hemibody RT for the remaining 2 months of life. © 2020 İpek Pinar Aral et al.
Keywords: CD3 antigen; CD4 antigen; CD8 antigen; clobetasol propionate; diphenhydramine; acanthosis; aged; Article; basement membrane; case report; cell vacuole; cerebrovascular accident; chronic obstructive lung disease; clinical article; coronary artery disease; cystitis; death; dermatologist; dermatology; dermis; epidermis; follow up; hospital admission; hospital patient; human; human tissue; hypertension; hypothermia; inflammation; low-dose radiotherapy; lymphocyte; male; multiple organ failure; mycosis fungoides; neutrophil chemotaxis; outpatient department; palliative therapy; paraplegia; priority journal; prurigo; pruritus; punch biopsy; upper limb